Kadar Protein Klebsiella pneumoniae Hasil Pemanasan 65 Derajat Celcius - Irawan Sugoro; Devita Tetriana (Al-Kauniyah: Jurnal Biologi, 2014)
Klebsiella pneumoniae is one of a coliform bacteria that causing mastitis. This disease were founded in dairy cows and can be prevented by vaccination. The research has been conducted to determine the inactive times, the protein concentration and profile of K. pneumoniae which inactivated by heating of 65oC as material of mastitis vaccine. The cells culture inactivated by the different times, i.e. 0, 10, 20, 30, 40, 50 and 60 minutes. The inactive times was determined by the drop test method, whereas the protein concentration of cells were determined by Lowry method. The results showed that the inactive times occured after 30 minute, and has a significant different on the protein concentration of bacteria cells that inactivated by the different times.